Laravel-Based Web Application for Alumni Books - Junaedi Adi Prasetyo; Amalia Eka Rakhmania; Della Priskilia (Politeknik Negeri Malang, 2022)
Alumni are an inseparable unit in the world of education. Alumni have a close relationship with the annual album book which is used to store alumni data. The alumni data at the Banyuwangi State Polytechnic is still kept in the form of an alumni album book. Data entered in printed form has many shortcomings, including the possibility of being damaged, lost, or not being able to be changed periodically. To overcome the above problems, making a Website-Based Alumni Book Application with the Laravel Framework is the right way to deal with these problems. With this alumni book application, users can store information data digitally and the data stored in this application can be updated regularly. The alumni book application provides a search feature that is used to quickly search alumni data and print alumni albums to print their own albums. In this alumni book application, users are given various kinds of information related to alumni. In addition, users can also view details of alumni annual albums from different graduating generations. Based on software testing carried out using the black box method, the Website-Based Alumni Book Application with the Laravel Framework which was tested at the Banyuwangi State Polytechnic has been in accordance with user needs and resulting the average for each page around 7MB.